051 Valproate and the risk for congenital malformations; is formulation and dosage regime important?. Issue 3 (9th February 2012) - Mawhinney, E; Campbell, J; Craig, J; Russell, A; Smithson, W; Parsons, L; Robertson, I; Irwin, B; Morrison, P; Liggan, B; Delanty, N; Hunt, S; et al.
Abstract : Background: Use of valproate in pregnancy, especially in doses over 1000mg a day, is known to be associated with a higher risk for major congenital malformations compared with other antiepileptic drugs. We sought to investigate whether the increased risk could be minimised by using controlled release or divided daily doses of valproate. Methods: The UK Epilepsy and Pregnancy Register is a prospective, observational and follow-up study set up to determine the risks of major congenital malformations for infants exposed to antiepileptic drugs in-utero. In this study we have extracted data for those pregnancies exposed to valproate in monotherapy. We have calculated malformation rates and relative risks as a function of valproate exposure. Results: Outcome data were available for 1109 pregnancies exposed to valproate in monotherapy. Exposure to over 1000 mg a day of valproate was associated with almost double the risk of major congenital malformation compared with daily valproate doses below 1000mg daily (8.86% vs 4.88%, RR: 1.7; 95% CI 1.1 to 2.9). There were no differences in the risks for malformations between standard release valproate and controlled release valproate preparations (RR: 1.11; 95% CI 0.67 to 1.83) or for those exposed to single or multiple daily administrations (RR: 0.99, 95% CI 0.58 to 1.70). Conclusion: Prescribing controlled release valproate or multiple daily administrations in pregnancy did not reduce the risk for malformations. Higher malformation rates observed with in utero exposure to valproate are more likely related to total daily dose, rather than peak serum levels.